Aberrant expression of glyceraldehyde-3-phosphate dehydrogenase (Gapdh) in warthin tumors - Mandic, Robert; Agaimy, Abbas; Pinto-Quintero, Daniel; Roth, Katrin; Teymoortash, Afshin; Schwarzbach, Hans; Stoehr, Christine; Rodepeter, Fiona R.; Stuck, Boris A.; Bette, Michael (Cancers, 2020)
The Warthin tumor represents the second most frequent benign tumor of the parotid gland and is characterized by the presence of oncocytes rich in structurally and functionally altered mitochondria. Next to its role in metabolism, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is also implicated in cellular mitophagy. Immunohistochemistry was carried out on Warthin tumor and normal control (parotid gland with striated ducts) tissues, using anti-GAPDH specific antibodies followed by digital image analysis. Laser capture microdissection was used to isolate the oncocytic tumor cell and normal control striated duct compartments for RNA extraction and qPCR. Warthin tumor oncocytes exhibited a markedly spotted GAPDH staining pattern exhibiting cells with cytoplasmic and nuclear, only nuclear or none GAPDH staining. A significantly lower (p < 0.0001) total GAPDH signal was detected in Warthin tumor oncocytes. Similarly, significantly lower (p < 0.005) GAPDH mRNA levels were seen in oncocytes compared with normal ductal cells. To exclude the possibility of this GAPDH staining pattern being a general feature of oncocytic neoplasms of different organs, we tested a cohort of renal oncocytoma and oncocytic chromophobe carcinoma; none showed this type of staining. The observed progressive GAPDH loss in Warthin tumor oncocytes could be implicated in the pathogenesis of Warthin tumors.
CRIS-Team Scopus Importer:2020-06-02
Keywords: GAPDH; Mitophagy; Oncocyte; Warthin tumor